A performer prepares : a guide to song preparation for actors, singers, and dancers - Craig, David, 1923-1998 (Applause acting series., 1993)
A PERFORMER PREPARES is a class act magically transformed to the printed page. It's a 13-part Master-class on how to perform, on any stage from bleak rehearsal room to the Palace Theatre. The class covers the basic Broadway and West End song numbers, from Show Ballad to Showstopper. With precise, logical steps and dynamic and entertaining dialogues between himself and his students, Craig takes anyone with the desire to shine from an audition to final curtain call. These lessons on the page recreate the unique interpersonal dynamic of Craig's legendary coaching encounters in New York and Los Angeles.